Informatics response to address the COVID-19 pandemic in a safety net healthcare system - Sadasivaiah, Shobha (JAMIA Open, 2021)
In service of particularly vulnerable populations, safety net healthcare systems must nimbly leverage health information technology (IT), including electronic health records (EHRs), to coordinate the medical and public health response to the novel coronavirus (COVID-19). Six months after the San Francisco Department of Public Health implemented a new EHR across its hospitals and citywide clinics, California declared a state of emergency in response to COVID-19. This paper describes how the IT and informatics teams supported San Francisco Department of Public Health’s goals of expanding the safety net healthcare system capacity, meeting the needs of specific vulnerable populations, increasing equity in COVID-19 testing access, and expanding public health analytics and research capacity. Key enabling factors included critical partnerships with operational leaders, early identification of priorities, a clear governance structure, agility in the face of rapidly changing circumstances, and a commitment to vulnerable populations.